PENDUGAAN KARBON PADA HUTAN KAWASAN CAGAR ALAM LO PAT FUN PIE KECAMATAN MONTERADO KABUPATEN BENGKAYANG - Widhanarto, Ganjar Oki; Simaremare, Emika; Dewantara, Iswan (JURNAL HUTAN LESTARI, 2024)
Trees are one of the constituents of natural forest stands that function as a place for storing or depositing carbon (carbon stock). The purpose of this study was to calculate the carbon content stored in forest stands in the Lo Pat Fun Pie Nature Reserve area. This research was conducted by systematic line plot sampling methode with non-destructive. Data collection technique using sampling plots and the IS taken is 10% with the number of sampling plots being 20 pieces and plot intervals of 63 m. In a 20 m x 20 plot, there are subplots measuring 10 m x 10 m for pile measurements and 5 m x 5 m for stake measurements. Tree, pole and sapling biomass was calculated using an allometric equation for tropical wood species in Indonesia.The results of the carbon estimation study in forest stands in the Lo Pat Fun Pie Nature Reserve area total the average AGC + UGC value was 124.83 tonsC/ha and for the overall estimated value of the standing population making up the Nature Reserve ± SD per ha was (602.46 ± 1,329 .85) tons C with the estimated median value of the population that is equal to 966.15 tonsC. Keywords: Carbon Stock, Estimation, Nature Reserves. Abstrak Pohon adalah sebagai salah satu penyusun tegakan hutan alam yang berfungsi sebagai tempat penimbunan atau pengendapan karbon (stok karbon). Tujuan penelitian ini untuk menghitung kandungan karbon tersimpan pada tegakan hutan yang terdapat pada kawasan Cagar Alam Lo Pat Fun Pie. Penelitian ini dilakukan dengan metode systematic line plot sampling dengan cara non-destruktive, dengan teknik pengumpulan data mengunakan petak sampling dan IS yang diambil adalah 10% dengan jumlah petak sampling adalah 20 buah dan interval plot 63 m. Dalam plot ukuran 20 m x 20 terdapat subplot berukuran 10 m x 10 m untuk pengukuran tiang dan 5m x 5m untuk pengukuran pancang. Biomassa pohon, tiang dan pancang dihitung menggunakan persamaan alometrik untuk jenis kayu tropis di Indonesia. Hasil penelitian pendugaan karbon pada tegakan Hutan di kawasan Cagar Alam Lo Pat Fun Pie jumlah Nilai rerata AGC + UGC sebesar sebesar 124,83 tonC/ha dan untuk nilai taksiran keseluruhan populasi tegakan penyusun Cagar Alam ± SD per ha sebesar (602,46 ± 1.329,85) tonC dengan nilai tengah dugaan dari populasi yaitu sebesar 966,15 tonC. Kata Kunci: Karbon Stok, Pendugaan, Cagar Alam